2005
DOI: 10.1111/j.1945-5100.2005.tb00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Petrographic, X-ray diffraction, and electron spin resonance analysis of deformed calcite: Meteor Crater, Arizona

Abstract: Abstract-Calcite crystals within the Kaibab limestone in Meteor Crater, Arizona, are examined to understand how calcite is deformed during a meteorite impact. The Kaibab limestone is a silty finegrained and fossiliferous dolomudstone and the calcite crystals occur as replaced evaporite nodules with impact-induced twinning. Twinning in the calcite is variable with deformational regimes based on abundances of crystals with twins and twin densities within crystals. The twins are similar to those that are seen in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…Attempts have also been made to quantify shock effects in carbonates using X-ray diffraction (XRD) and electron spin resonance (ESR) (Polanskey and Ahrens 1994;Skála and Jakeš 1999;Skála et al 2002;Burt et al 2005); however, calibration of the observed effects with respect to shock pressure remains ambiguous so that these methods remain qualitative at present. Recently, the first detailed application of twin analysis in calcite has been used to quantify shock pressures in carbonates from Serpent Mound, USA (Schedl 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have also been made to quantify shock effects in carbonates using X-ray diffraction (XRD) and electron spin resonance (ESR) (Polanskey and Ahrens 1994;Skála and Jakeš 1999;Skála et al 2002;Burt et al 2005); however, calibration of the observed effects with respect to shock pressure remains ambiguous so that these methods remain qualitative at present. Recently, the first detailed application of twin analysis in calcite has been used to quantify shock pressures in carbonates from Serpent Mound, USA (Schedl 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that at these temperatures and pressures, twins in calcite crystals barely contribute to the X-ray peak broadening. [28] In light of these considerations it is reasonable to conclude that an increase in the microstrain fluctuations in biogenic crystals with respect to their geological counterparts is caused by organic macromolecules that are an integral part of these biocomposites. The organic macromolecules produce inhomogeneous deformation fields on a nanometer scale that are "detected" by X-rays.…”
mentioning
confidence: 97%
“…Structural rearrangements of carbonates are possible, as various polymorphs of a number of carbonate minerals are known, occurring both at ambient conditions (Chang et al, 1998), and at elevated pressures (e.g., Isshiki et al, 2003;Sekine et al, 2006;Ono et al, 2007). Carbonates from impact craters can exhibit peak-broadening in Xray diffraction data, but the cause of this broadening is not well understood (e.g., Burt et al, 2005;Huson et al, 2006). The sensitivity of carbonates to different processes, such as exposure to the Martian surface environment, impact heating and pressures, and tectonic forces is only poorly constrained at present.…”
Section: Article In Pressmentioning
confidence: 97%